Design and application of a technique monitoring system for rip entry movement in diving - Zhou, J.; Li, X.; Li, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The technique of diving consists of walking on the springboard, takeoff, swiveling, opening, water entry and movements under water. The rip entry movement is the most difficult as it is based on swiveling and then the entry. Thus, this study designed a technique monitoring system for the rip entry movement to obverse this movement above water and to monitor a series of underwater movements. Findings will provide a scientific reference for training. Methods The technique monitoring system for rip entry movement is comprised of an underwater camera, above water camera, screen synthesizer, recorder, computer and analysis software. The principle based on a is synchronous record screens from cameras underwater and above water into a screen synthesizer which patches two screens together and then sends images to a recorder or computer. Therefore, after each dive, athletes can obverse their continuous actions. It was applied under both competitions[1][2] and training conditions. Conclusions The system proved to be simple and convenient when applied to both competition and training. The feedback of screens and figures is fast and easy to operate. Plane kinematical figures are available at the competition site. The model of rip entry movement showed the movement is characterized by quick actions, tight arms and smooth water entry. Quick action means the swiveling and opening actions should finish rapidly in order to increase the rotation inertia and decrease rotation velocity. Tight arms means muscles of the arms should be tight and fixed and both hands should be closed in order to ensure a larger square of rip entry. Smooth water entry means athletes should enter the water breaking with the rear of hands.